2014
DOI: 10.1103/physrevlett.113.128305
|View full text |Cite
|
Sign up to set email alerts
|

Weighing Polyelectrolytes Packaged in Viruslike Particles

Abstract: This Letter reports on the remarkable selectivity of capsid proteins for packaging synthetic polyelectrolytes in viruslike particles. By applying the contrast variation method in small-angle neutron scattering, we accurately estimated the mean mass of packaged polyelectrolytes ⟨Mp⟩ and that of the surrounding capsid ⟨Mcap⟩. Remarkably, the mass ratio ⟨Mp⟩/⟨Mcap⟩ was invariant for polyelectrolyte molecular weights spanning more than 2 orders of magnitude. To do so, capsids either packaged several chains simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…We performed static measurements by small-angle neutron scattering (SANS) with a mixture of subunits and genome in 68% D 2 O at pD 7.5. In this fraction of heavy water, the contrast between RNA and the solvent vanishes, and solely the scattering intensity arising from the proteins is detected 6 . The subunit-to-genome mass ratio ρ in a native virion is about 3.6, but we performed experiments with ρ around 6, which has been found to be the minimal ratio ensuring the complete packaging of genome 43 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We performed static measurements by small-angle neutron scattering (SANS) with a mixture of subunits and genome in 68% D 2 O at pD 7.5. In this fraction of heavy water, the contrast between RNA and the solvent vanishes, and solely the scattering intensity arising from the proteins is detected 6 . The subunit-to-genome mass ratio ρ in a native virion is about 3.6, but we performed experiments with ρ around 6, which has been found to be the minimal ratio ensuring the complete packaging of genome 43 .…”
Section: Resultsmentioning
confidence: 99%
“…The genome is packaged during replication in the host cell 1 through an efficient self-assembly process 2 4 . The fact that some viruses are able to self-assemble from purified components and to package materials in vitro has promoted the development of engineered viral capsids enclosing synthetic polymers 5 , 6 , heterologous nucleic acids 7 10 , nanoemulsion droplets 11 , gold 12 , 13 , and magnetic 14 nanoparticles to name a few. Therefore, understanding the molecular mechanisms of viral self-assembly can help devise therapeutic strategies for inhibiting viral replication 15 , 16 and design functional biocompatible nanocontainers 17 for drug delivery and medical imaging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, it seems that there is a trade-off between the stiffness of the polymer to be encapsulated and the strength of the protein-protein interactions (35,37,39). CCMV has, for instance, a preference for packaging of polystyrene sulfonate (PSS), which favors a collapsed state over singlestranded RNA, which acts like a many-branched polymer (43). For SV40, it is shown that tertiary structure of PSS or RNA and the size of the substrate affect the assembly (19).…”
Section: Discussionmentioning
confidence: 99%
“…structure determination. In reviewing several previous works that involved the formation of T ¼ 2-sized particles made from CCMV or BMV CPs, it appears that all of these assemblies have resulted in heterogeneous particles (8,29,30,(32)(33)(34). A mutated CCMV CP lacking most of its cationic N-terminal domain has been shown to produce, in vitro, heterogenous, T ¼ 2-sized particles, in addition to producing T ¼ 1 and T ¼ 3 particles.…”
Section: Discussionmentioning
confidence: 99%